2021
DOI: 10.3390/ijerph181910280
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ with Multimorbidity and Psychosocial Difficulties and Their Views on Important Professional Competence for Rehabilitation Coordinators in the Return-to-Work Process

Abstract: Coordinators may play a key role during the return-to-work (RTW) process for people on sickness absence. There are still few studies on the newly implemented rehabilitation coordinators (RECO) within Swedish healthcare, and none focus on their competence. The aim of this study was to explore how persons with multimorbidity and psychosocial difficulties describe the professional competence of the RECO they encountered during their RTW process. The study takes a relational and practical approach in defining prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Within this study, participants mainly valued not being alone with problems, case managers motivating them and feeling understood. This was previously discussed as being persistent [ 21 ]. Furthermore, participants described that they achieved realistic expectations during the intervention concerning their future.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Within this study, participants mainly valued not being alone with problems, case managers motivating them and feeling understood. This was previously discussed as being persistent [ 21 ]. Furthermore, participants described that they achieved realistic expectations during the intervention concerning their future.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, in a qualitative study assessing the experience of people with multimorbidity utilizing a rehabilitation coordinator during sickness absence, individuals describe the fear of not being appropriately consulted by the employment services or that contacting the social insurance agency was difficult [ 18 ]. On the other hand, the coordinating role of case managers or other RTW professionals was described as facilitating in several studies [ 18 , 19 , 20 ], with e.g., helping to adjust individuals strategies for RTW [ 20 ] or helping to stabilize work motivation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The patients’ perspective is, therefore, important for optimizing the coordination efforts. Previous studies of the patient perspective on coordination are based on interviews with small numbers of participants [ 19 , 20 , 21 , 22 , 23 ]. These studies have found that RTWCs are perceived to enhance communication and collaboration between stakeholders and the transfer of knowledge between them.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, rehabilitation coordinators (RCs) have been introduced in the Swedish health care system. Their role is to provide individual support to sick-listed patients and to coordinate with other public services and employers in the RTW process (29). RCs work both in primary care and inpatient care, and since February 2020, all regions in Sweden are obliged to offer RC services to sick-listed patients that need it.…”
Section: Introductionmentioning
confidence: 99%